Human Papillomavirus Detection and Abnormal Anal Cytology in HIV-infected Patients Using p16/Ki-67 Dual-Staining - Patarapadungkit, Natcha (Asian Pac J Cancer Prev, 2020)
OBJECTIVE: We investigated human papillomavirus (HPV) infection and detected anal squamous intraepithelial lesions by modified liquid-based cytology (LBC) and p16/Ki67 dual-staining. METHODS: Anal swabs (n=393) were collected from patients with HIV infection. Anal cells were kept in 95% ethyl alcohol for modified LBC. DNA was extracted from cells for HPV detection and genotyping using real-time PCR and reverse line blot hybridization. Results: Nine samples (2.3%) were unsatisfactory specimens, 74.8% (294/393) were negative for intraepithelial malignancies (NILM) and 22.9% (90/393) exhibited squamous intraepithelial lesions (SIL). In the latter category, 13.7% of samples (54/393) contained atypical squamous cells of undetermined significance (ASCUS), 6.9% (27/393) were classified as low-grade SIL (LSIL) and 2.3% (9/393) as high-grade SIL (HSIL). A total of 331 from 393 swab samples were suitable for detection of HPV infection. Among these, 34.1% (113/331) were positive. HPV 58 (15.9%) was the most common genotype, followed by HPV 18 (14.2%) and HPV 16 (11.5%). The severity of abnormal cells was significantly associated with HPV infection. Dual staining with p16/Ki-67 was performed on 130 samples: in 30.8% (40/130) of samples positive staining was significantly associated with severity of abnormal cells. Agreement between cytology, p16/Ki67 dual-staining and high-risk HPV detection was 100% in HSIL samples. Interestingly, eight apparently NIML cases might have contained abnormal cells, since they were positive by both p16/Ki67 dual-staining and high-risk HPV detection. CONCLUSION: Anal specimens screened using modified LBC with 95% ethyl alcohol solution as the fixative are suitable for screening anal precancerous lesions by cytology, HPV testing and p16/Ki-67 dual staining.